1996
DOI: 10.1086/176827
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Coma Cluster

Abstract: We examine the structure and dynamics of the galaxies in the Coma cluster using a catalog of 552 redshifts including 243 new measurements. The velocity distribution is shown to be non-Gaussian due to structure associated with the group of galaxies around NGC4839, 40 arcmin SW of the cluster core. We apply a mixture-modelling algorithm to the galaxy sample and obtain a robust partition into two subclusters which we use to examine the system's dynamics. We find that the late-type galaxies are freely-falling into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
465
3
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(504 citation statements)
references
References 31 publications
(51 reference statements)
35
465
3
1
Order By: Relevance
“…We put the centre of this second component at (RA, Dec) = (12 h 56 m 59 s , +27 • 29 27 ) and fix all the shape parameters of its pressure profile to the "universal" shape given by Arnaud et al (2010). The pressure amplitude of the group is fixed to 10% of the mass of the Coma cluster, which is the upper limit from dynamical observations (Colless & Dunn 1996). This leads to a PTE of only 0.005, implying that NGC 4839 with 10% of the Coma mass is insufficient to produce the observed pressure excess.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We put the centre of this second component at (RA, Dec) = (12 h 56 m 59 s , +27 • 29 27 ) and fix all the shape parameters of its pressure profile to the "universal" shape given by Arnaud et al (2010). The pressure amplitude of the group is fixed to 10% of the mass of the Coma cluster, which is the upper limit from dynamical observations (Colless & Dunn 1996). This leads to a PTE of only 0.005, implying that NGC 4839 with 10% of the Coma mass is insufficient to produce the observed pressure excess.…”
Section: Resultsmentioning
confidence: 99%
“…Observations with XMM-Newton (Neumann et al 2001) revealed a complex temperature structure around the group, which suggests the group to be at its first infall into Coma. We model the group as a second GNFW component with 1/10 the mass of the Coma cluster, which is the upper mass limit derived from a dynamical analysis (Colless & Dunn 1996). Alternatively, we let the mass be a free parameter, i.e.…”
Section: Modelsmentioning
confidence: 99%
“…In this paper, we use Rvir to define the virial radius of a galaxy cluster, such that the mean density inside this radius is 100 times the critical density of the universe at that redshift, consistent with the definitions in Bryan & Norman (1998 Colless & Dunn (1996a) 972 Table 1. The virial radius, virial mass, ICM gas temperature, and velocity dispersion of the Virgo and Coma galaxy clusters in comparison with the simulated Virgo-like and Coma-like clusters.…”
Section: Enzo Simulationmentioning
confidence: 99%
“…At low redshifts, there are many other examples of merging clusters or galaxy groups falling onto clusters along filamentary structure. To mention a few: Coma (Colless and Dunn 1996;Adami et al 2005), A 521 , A 754 (Henry et al 2004), A 2199 (Rines et al 2001), A 2219 (Boschin et al 2004), A 3560 in the Shapley supercluster (Bardelli et al 2002), A 3921 . At high redshift the number of irregular and merging clusters increases substantially (Rosati 2004;Kodama et al 2007).…”
Section: Substructure Mass Accretion and Non-thermal Phenomenamentioning
confidence: 99%